Pengaruh Penggunaan Jaring Berwarna Terhadap Kelimpahan Serangga Aphis gossypii pada Tanaman Cabai Rawit (Capsicum frutescens L.) - UTAMI, NYOMAN AYU TRISNA ARI; WIJAYA, I NYOMAN; SIADI, I KETUT; NYANA, I DEWA NYOMAN; SUASTIKA, GEDE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2014)
ABSTRACT Effect of Barier Colored Nets to Abundance of Aphis gossypii on Cayenne Pepper ( Capsicum frutescens L .) Cayenne pepper ( Capsicum frutescens L.) is a plant that has a high economic value and has a many of uses that as seasoning at household, as an ingredient in various food processing industries and the manufacture of pharmaceuticals. Currently chili productivity in Indonesia is still low therefore needs a national chili can not be optimally. One reason is the insect infestation of   A. gossypii are a double role as pests and disease vectors. The use of red and white netting barier around planting chili is one of the pest control management that is environmental friendly. The purpose of this study was to determine the role of red-and-white nets barier in protect the entry of A. gossypii in chilli planting area. There are three treatments were tested using a red netting, white netting and planting without the use of nets. The results showed that the use of red and white nets can reduce insect populations of A. gossypii on peppers planting area. Average of the highest populations of A. gossypii on treatment without a net, then the white netting treatment and lowest in the red, so that the use of red nets can be used to reduce the population of A. gossypii on chilli crop.   Keywords : Chilli pepper , A. gossypii, colored nets
Keywords: Chilli pepper; A. gossypii; colored nets